Implementasi Sistem Monitoring Zabbix Dan Discord Webhook Untuk Nontifikasi Real-time Server - Maria Afri Yani; Dia alemisa br Sembiring; Lotar Mateus Sinaga (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Server monitoring is an important aspect of maintaining the availability, reliability, and performance of information technology services. Delays in detecting server disruptions can lead to decreased service quality, increased downtime, and hindered operational processes. Therefore, a monitoring system capable of providing fast and accurate information about server conditions to administrators is required. This study aims to implement a monitoring system using Zabbix integrated with Discord Webhook as a real-time notification medium. The research method includes problem identification, literature review, system requirements analysis, implementation, and system testing. The implementation was carried out through network topology design, installation and configuration of the Zabbix Server on the Debian 12 operating system, creation of monitoring hosts using the ICMP Ping method, and integration of Discord Webhook for automatic notification delivery. Testing was conducted by simulating disruptions on the Debian 12 server to trigger problem and recovery conditions in Zabbix. The results show that the system successfully detected the conditions of Unavailable by ICMP Ping and High ICMP Ping Loss automatically. In addition, both disruption and recovery notifications were successfully sent to a Discord channel in real time according to changes in server status. The implementation of this system can assist network administrators in monitoring server conditions more effectively, accelerate the process of identifying disruptions, and improve responses to network problems without having to continuously access the Zabbix dashboard.